2003
DOI: 10.1002/pon.682
|View full text |Cite
|
Sign up to set email alerts
|

Travelling for radiation cancer treatment: Patient perspectives

Abstract: Radiation treatment for cancer requires patients to receive frequent administrations and attend the treatment facility on a daily basis for several weeks. Travelling for radiation treatment has the potential to add to the distress an individual may be feeling. This study utilized in-depth interviews to capture 118 patients' perspectives about travelling for cancer treatment. Four themes emerged during the analysis of the data: (1) waiting was the most difficult part of the experience; (2) the idea of travellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 19 publications
4
73
0
17
Order By: Relevance
“…A Canadian study on travel issues [38] confirmed the challenges of travel reported in quantitative studies. Four themes emerged: (1) waiting was the most difficult part of the experience.…”
Section: Table 3 About Herementioning
confidence: 60%
See 4 more Smart Citations
“…A Canadian study on travel issues [38] confirmed the challenges of travel reported in quantitative studies. Four themes emerged: (1) waiting was the most difficult part of the experience.…”
Section: Table 3 About Herementioning
confidence: 60%
“…There were 14 quantitative studies without a control group, three on emotional aspects, three on travel issues and eight on needs and quality of life, all in the active phase of treatment [9,11,[26][27][28][29][30][31][32][33][34][35][36][37]. Only one study [35] was longitudinal.…”
Section: Quantitative Studies With No Control Groupmentioning
confidence: 99%
See 3 more Smart Citations